ISLAMIC ETHICS BASED ON AL-QUR'AN AND MULLA ṢADRĀ’S ESCATOLOGY - Kerwanto, Kerwanto (Teosofia: Indonesian Journal of Islamic Mysticism, 2015)
Mulla á¹¢adrÄ is one of the philosophers who provide philosophical views and answers to the principles of eschatology (ma'Äd) that have not been answered by the philosophers of his predecessors. He is also known for successfully pouring his philosophical thoughts in his various commentaries on the main religious sources, both those relating to the Qur'an and á¸¥adÄ«th. In this paper, there are several principles of eschatology of á¹¢adrÄ which the writer will examine as the position of á¹¢adrÄ in regard to post-mortal physical resurrection, the intellectual (intellectual) (intellectual), the role of the Actor (fÄ'il) and Action ('amal) and the relationship between resurrection (ma'Äd) and ethics (AkhlÄk). In the eschatology of á¹¢adrÄ, the knowledge of eschatological matters (life akherat) has a major influence on an individual's ethical actions. This paper is also intended to show that Mulla á¹¢adrÄ's ethics as an implication of his eschatological philosophy is synergistic with the main sources of religion; Both the Qur'an and the Hadith of the Prophet.